5 - Impact of Covid-19 Pandemic on the Financial Performance of SMEs in Nigeria: A Study of the South East Geopolitical Zone - Stella Okoroafor, (Africa Development, 2023)
This article explores the impact of the Covid-19 pandemic on the financial performance of small and medium-scale enterprises (SMEs) in the South East geopolitical zone of Nigeria. The study objective was to determine the extent to which the Covid-19 pandemic affected the revenue of SMEs, their profitability and their access to credit. The target population for the study were registered SMEs in the South East geopolitical zone of Nigeria, being Abia, Anambra, Ebonyi, Enugu and Imo. Using purposive sampling method, thirty SME owners from each zone were selected for the study, giving a total of 150 SME owners. The study adopted a quantitative research method, using a questionnaire. The findings revealed that the Covid-19 pandemic significantly reduced the profitability and revenue of SMEs but not their access to credit. The study therefore recommended the need for business owners to minimize cost and look for possible innovations/opportunities to grow sales and improve revenue. Also government should make soft loan available to SMEs to help cushion the effect of the pandemic on their financial performance. Finally, future research should consider other related variables that have not been covered in this article.